Incentives for separation and incentives for public good provision - Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper I examine the incentives of regions to unite, to separate and to provide public goods. Separation allows for greater influence over the nature of political decision making while unification allows regions to exploit economies of scale in the provision of public goods. When public good provision is relatively inexpensive, separation occurs since individuals want to assert greater influence, while for intermediate costs of public good provision, separation can be explained by the desires for greater influence as well as for more public goods. Compared with the social optimum, there are excessive incentives for public good provision as well as excessive incentives for separation.
urn:nbn:de:bvb:19-epub-13447-2
Keywords: D7; H2; H7; 330; unification; separation; public good provision; voting